The Influence of Initial Mathematical Ability and Numbered Head Together Type Cooperative Learning Model on Mathematical Communication Ability and Self Efficacy - Jannah, Fathul; Simamora, Elmanani; Syahputra, Edi (Jurnal Perspektif, 2025)
This study aims to determine:  The effect of initial mathematical ability on students' mathematical communication ability;  The effect of initial mathematical ability on students' self-efficacy; The effect of cooperative learning model type numbered heads together and direct learning on students' mathematical communication ability; The effect of cooperative learning model type numbered heads together and direct learning on students' self-efficacy; The interaction between initial mathematical ability and learning model on mathematical communication ability; The interaction between initial mathematical ability and learning model on self-efficacy. This study is a quantitative study with a quasi-experiment. The sample of this study was 62 students of MAN 1 Medan class X, with a two-way ANOVA analysis. The results of the study showed that:  There is an influence of initial mathematical abilities on students' mathematical communication abilities; There is an influence of initial mathematical abilities on students' self-efficacy;There is an influence of the cooperative learning model type numbered heads together and direct learning on students' mathematical communication abilities; There is an influence of the cooperative learning model type numbered heads together and direct learning on students' self-efficacy; There is no interaction between initial mathematical abilities and learning models on mathematical communication abilities; There is no interaction between initial mathematical abilities and learning models on self-efficacy.